2022
DOI: 10.3390/healthcare10122469
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on Physical Activity and Psychological Distress in Adults with Asthma

Abstract: Physical Activity (PA) could contribute to decreasing psychological distress and improving Self-Perceived Health (SPH) in adults with Asthma. The main objective of this study was to analyse the associations between the Physical Activity Level (PAL) Perceived Social Support (PSS) and Mental Health, using the Goldberg General Health Questionnaire (GHQ-12), and SPH in the adult population with Asthma. This descriptive cross-sectional study is based on data from the 2017 Spanish National Health Survey, including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Suggestions for the best amount and highest limit of physical activity to decrease anxiety symptoms have been proposed for the general population ( Kim et al, 2020 ), and both resistance and aerobic exercise have been shown to improve anxiety and psychological distress ( LeBouthillier & Asmundson, 2017 ). In line with the present findings, PA has been also reported to be inversely correlated with successful coping and self-esteem in adults with asthma ( Denche-Zamorano et al., 2022e ), the same was found for these two variables and also for stress in adults with depression ( Denche-Zamorano et al., 2022d ), in adults with cancerous tumours ( Franco-García et al, 2023 ) and in a population of informal caregivers ( Denche-Zamorano et al., 2022c ). Successful coping ability ( Craven et al, 2022 ; Dahlstrand et al, 2021 ; Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ), stress ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) and self-steem ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) seem to be improved by performing PA, which supports the available research that suggests the potential of PA on the prevention of depression, anxiety and other mental disorders ( Harvey et al, 2010 ; Herring, Lindheimer & O’Connor, 2014 ; Ji et al, 2022 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; Schuch et al, 2019 ; Stubbs et al, 2017 ; Wijndaele et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Suggestions for the best amount and highest limit of physical activity to decrease anxiety symptoms have been proposed for the general population ( Kim et al, 2020 ), and both resistance and aerobic exercise have been shown to improve anxiety and psychological distress ( LeBouthillier & Asmundson, 2017 ). In line with the present findings, PA has been also reported to be inversely correlated with successful coping and self-esteem in adults with asthma ( Denche-Zamorano et al., 2022e ), the same was found for these two variables and also for stress in adults with depression ( Denche-Zamorano et al., 2022d ), in adults with cancerous tumours ( Franco-García et al, 2023 ) and in a population of informal caregivers ( Denche-Zamorano et al., 2022c ). Successful coping ability ( Craven et al, 2022 ; Dahlstrand et al, 2021 ; Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ), stress ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) and self-steem ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) seem to be improved by performing PA, which supports the available research that suggests the potential of PA on the prevention of depression, anxiety and other mental disorders ( Harvey et al, 2010 ; Herring, Lindheimer & O’Connor, 2014 ; Ji et al, 2022 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; Schuch et al, 2019 ; Stubbs et al, 2017 ; Wijndaele et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the present findings, PA has been also reported to be inversely correlated with successful coping and self-esteem in adults with asthma ( Denche-Zamorano et al., 2022e ), the same was found for these two variables and also for stress in adults with depression ( Denche-Zamorano et al., 2022d ), in adults with cancerous tumours ( Franco-García et al, 2023 ) and in a population of informal caregivers ( Denche-Zamorano et al., 2022c ). Successful coping ability ( Craven et al, 2022 ; Dahlstrand et al, 2021 ; Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ), stress ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) and self-steem ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) seem to be improved by performing PA, which supports the available research that suggests the potential of PA on the prevention of depression, anxiety and other mental disorders ( Harvey et al, 2010 ; Herring, Lindheimer & O’Connor, 2014 ; Ji et al, 2022 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; Schuch et al, 2019 ; Stubbs et al, 2017 ; Wijndaele et al, 2007 ). Despite the correlations found among PAL and GHQ-12 items and dimensions, and the available research supporting that performing greater PA is associated with a better mental state, cause–effect relationships cannot be stablished between performing larger PA and a better state in the dimensions evaluated by GHQ-12, including mental health.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Pharmacological stepwise therapy is the first line of treatment for asthma. Current treatment guidelines for this disease highlight management with inhaled corticosteroids alone or in combination with a long-acting beta-agonist [2][3][4].…”
Section: Introductionmentioning
confidence: 99%